2021
DOI: 10.1007/s00787-021-01861-z
|View full text |Cite
|
Sign up to set email alerts
|

Child, parent, and family mental health and functioning in Australia during COVID-19: comparison to pre-pandemic data

Abstract: The COVID-19 pandemic presents significant risks to population mental health. Despite evidence of detrimental effects for adults, there has been limited examination of the impact of COVID-19 on parents and children specifically. We aim to examine patterns of parent and child (0–18 years) mental health, parent substance use, couple conflict, parenting practices, and family functioning during COVID-19, compared to pre-pandemic data, and to identify families most at risk of poor outcomes according to pre-existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
139
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 69 publications
(96 reference statements)
12
139
1
4
Order By: Relevance
“…These results align with previous parent-report research suggesting that parents with children at home have been a population at heightened risk of worsened mental health outcomes during the pandemic [6,10,15]. As other studies have identified, a confluence of stressors on families, including economic pressures, balancing multiple demands and disruptions, and increased relational stress, has been associated with poorer mental health and burnout [10,15,35,36]. The current study also identified social disparities in mental health outcomes that concur with past research [15,37].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results align with previous parent-report research suggesting that parents with children at home have been a population at heightened risk of worsened mental health outcomes during the pandemic [6,10,15]. As other studies have identified, a confluence of stressors on families, including economic pressures, balancing multiple demands and disruptions, and increased relational stress, has been associated with poorer mental health and burnout [10,15,35,36]. The current study also identified social disparities in mental health outcomes that concur with past research [15,37].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with research in the United States that found parents reported a high level of closeness with their children during the pandemic, as well as increased conflicts, discipline, and harsh words [34]. It contrasts with research in Australia that found decreases in family positive expressiveness during the pandemic [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although we cannot assume a causal link, this finding suggests that caregivers’ mental health may have also declined during the pandemic, and this could be an important point of intervention. There is a growing body of literature documenting the negative impacts of the pandemic on caregiver mental health, including a study among 3000 Canadian adults [ 53 ] showing worse mental health among parents with minor children at home compared to other adults, and a study showing increased depression, anxiety, and stress among 2365 Australian parents compared to pre-pandemic estimates [ 54 ]. This study also found that worse parent functioning was related to pre-existing parent and child physical and mental health conditions, These findings suggest that intervening on the caregiver and family level may be all the more important for children with mental health problems during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Providing evidence of these risks, parents in particular reported heightened levels of stress and depression along with declines in well-being in the initial months of the pandemic (see Aknin et al, 2021;Feinberg et al, 2021;Westrupp et al, 2021). Increases in parents' distress, in turn, have been linked to less responsive parenting (e.g., Brown et al, 2020;McRae et al, 2021).…”
Section: Parents' Health and Family Functioning Across The Pandemicmentioning
confidence: 99%